Trends of Potential Fishing Zones (PFZs) along the Mumbai coast, Maharashtra - Kamei, Gaihiamngam; F. Felix, Jasmin; Shenoy, Latha; Shukla, S. P. (Indian Journal of Fisheries, 2014)
The Potential Fishing Zones (PFZs) advisory from INCOIS, Hyderabad for Mumbai coast was analysed to study the trend of PFZ locations. The PFZ trends for landing centers of Versova, Mahim and Colaba were studied during the period 2010-2011. The average depth and distance were 55.2 m and 100 km respectively from the coast in 2010. In the year 2011, the average depth and distance were calculated at 37.8 m and 59 km respectively. The PFZ areas located ranged from 5-229 km in distance and 12-97 m in depth during 2010 and 22-1000 km in distance and 17-500 m in depth in 2011.